Epigraphs. Desirable Imaginations and other Epistemes - Russi, Pedro (2020)
DOI: 10.26439/contratexto2020.n033.4790 The proposal is to open the discussion, from oral epistemology, as the basis for other epistemologies, to think about communication to imagine desirable futures for Latin America. The idea of feeling as a decentralization of the perspectives that make it possible to understand open educational processes in the uncertainty of the answers. Do not follow models, molds or manuals, but the power of the imagination as a resistance strategy against the dogmas that are installed as ways of thinking. It is the interlocutions that potentiate new questions that should not necessarily be answered. They serve to question better. We cannot understand the action of imagining but we understand the episteme of the interlocutions that pass us through time, to imagine is to be in miscellaneous. Today, especially, imagining is one of the forms of resistance.